Preparation and Functional Activity of Nano-silver Materials for Dried Ginger - Junjie WU; Wenya JIAO; Yu ZHANG; Jinhao SUN; Xianghong WANG (Shipin gongye ke-ji)
To address the lengthy and pollution-intensive process of traditional nano-silver synthesis, This paper developed a method using dried ginger extract, which was rich in active substances. This paper investigated the effects of various factors, including the concentration of dried ginger extract, silver nitrate concentration, heating temperature, and heating time, on nano-silver synthesis through single-factor experiments. The synthesized nano-silver was characterized using ultraviolet-visible (UV-Vis) absorption spectroscopy, transmission electron microscopy (TEM), Zeta potential measurement, Fourier transform infrared (FTIR) spectroscopy, and thermal stability analysis. Additionally, its antibacterial and antioxidant activities were examined. The optimized synthesis conditions were found to be: 16 mg/mL dried ginger extract, 0.02 mol/L silver nitrate (AgNO3), a temperature of 60 ℃, and a heating time of 155 min. Under these conditions, the nano-silver exhibited a distinct UV absorption peak at 418 nm, a spherical shape, an average particle size of 22.43 nm, a lattice spacing of 0.2325 nm, good dispersibility, and a face-centered cubic structure. The scavenging capacities of 100 μg/mL nano-silver for DPPH and ABTS+ free radicals were 50% and 52.2%, respectively. The minimum inhibitory concentration (MIC) and 2MIC of silver nanoparticles significantly inhibited the growth of Erwinia carotovora, Pseudomonas fluorescens, Bacillus subtilis, Escherichia coli, Staphylococcus aureus, and Listeria monocytogenes. The inhibitory mechanism involved disrupting the cell membrane structure, leading to leakage of cellular contents and bacterial death. The nano-silver produced by this method demonstrates good stability and holds promising potential for applications in fruit and vegetable preservation and biomedicine.